MODEL PEMBERDAYAAN BUMDES DAN SOLUSI PEMBANGUNAN EKONOMI DESA: SUATU KAJIAN LITERATUR - Azhari, Azhari (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2019)
The purpose of this conceptual research is to explain the understanding of the Village Owned Enterprise (BUMDes) empowerment model and the Village Economic Development Solution. This research uses the literature review method from various sources of expert opinions and references. The results of the study that the BUMDes empowerment model is through Business Plan, SWOT Analysis while the village economic development solutions through the principles of Participation, Openness, Accountability, Sustainability and Enjoyed by the community. BUMDes can prevent unemployment, poverty, create employment and Village Original Income (PAD). Keywords: Empowerment, BUMDes, Village Economic Development. Abstrak Tujuan dari penelitian konseptual ini adalah untuk menjelaskan pemahaman tentang model pemberdayaan Badan Usaha Milik Desa (BUMDes) dan Solusi Pembangunan Ekonomi Desa. Penilitian ini menggunakan metode kajian literatur dari berbagai sumber pendapat para ahli dan referensi. Hasil kajian bahwa model pemberdayaan BUMDes adalah melalui Business Plan, Analisis SWOT sedangkan solusi pembangunan ekonomi desa melalui prinsip Partisipasi, Keterbukaan, Dipertanggungjawabkan, Berkelanjutan dan Dinikmati masyarakat. BUMDes dapat mencegah pengangguran, kemiskinan, menciptakan lapangan kerja dan Pendapatan Asli Desa (PAD). Kata kunci: Pemberdayaan, BUMDes, Pembangunan Ekonomi Desa.